2021
DOI: 10.1111/1467-8500.12474
|View full text |Cite
|
Sign up to set email alerts
|

Building a culture of innovation: How do agency leadership and management systems promote innovative activities within the government?

Abstract: Public organisations have strived to initiate and consolidate innovation by reforming their structures, processes, and outcomes. Despite their numerous attempts, 454 PARK et al.term, even if innovation performance improves in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 68 publications
0
7
0
3
Order By: Relevance
“…Scholars called for research to enhance understanding of the antecedents of IWBs at the individual level of analysis (Demircioglu & Van der Wal, 2022). Previous research has identified the importance of supportive leadership in promoting IWBs, which are argued to be crucial to NPO's sustainability (do Adro & Leitão, 2020; Park et al., 2021). This study adds to existing research about IWBs by examining the proposition that authentic leadership and tolerance of change frequency and uncertainty are key antecedents of IWBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars called for research to enhance understanding of the antecedents of IWBs at the individual level of analysis (Demircioglu & Van der Wal, 2022). Previous research has identified the importance of supportive leadership in promoting IWBs, which are argued to be crucial to NPO's sustainability (do Adro & Leitão, 2020; Park et al., 2021). This study adds to existing research about IWBs by examining the proposition that authentic leadership and tolerance of change frequency and uncertainty are key antecedents of IWBs.…”
Section: Discussionmentioning
confidence: 99%
“…This paper addresses this gap by examining whether authentic leadership is associated with non-profit organisation (NPO) employees' acceptance of change and IWBs. Park et al (2021) posit that supportive leadership is the key to sustaining an innovative culture. This study builds on the work of do Adro and Leitao (2020) and Demircioglu and Van der Wal (2022) by examining whether authentic leadership is the missing ingredient required to build an 'innovation-enabling' culture likely to promote acceptance of change and IWB.…”
Section: Introductionmentioning
confidence: 99%
“…Supportive leadership has received considerable attention in the leadership (House, 1971) and mentoring literature (Allen et al, 2004) and recently in the public management literature as well (Park et al, 2021). It represents a relational leadership behaviour that provides followers with emotional, informational, instrumental and appraisal support (House et al, 2004;Rafferty and Griffin, 2006).…”
Section: Supportive Leadership and Organisational Practicesmentioning
confidence: 99%
“…According to the existing literature, successful organizational innovation involves modifying various organizational components such as structure, processes, and culture in ways that help the organization achieve its desired goals, such as maximizing the chances of its survival or adapting more effectively to a changing organizational environment (Hadi, 2022;Hidayati et al, 2022;Park et al, 2021). In an organization, innovation occurs in the form of introducing a newly implemented system, which makes an organization more mature and able to compete.…”
Section: Introductionmentioning
confidence: 99%